Method for preparing graphene-based conducting nano-composite film - Lim, Hong Ngee; Eeu, Yik Chong; Zakarya, Salwani Asyikin; Huang, Nay Ming; Lim, Yee Seng (2013)
A method for preparing graphene-based conducting nano-composite film includes the steps of, providing a graphite source and oxidizing the graphite source to form graphite oxide solution, creating a dispersion of the graphite oxide solution in a liquid, thickening the graphite oxide solution to form a graphite oxide gel, providing a deposition solution and dipping it in the graphite oxide gel, providing a substrate, and, applying an electric field across at least a portion of the deposition solution dipped in the graphite oxide gel for depositing at least one portion of graphene from the graphite oxide gel and the deposition solution on the substrate.